2013
DOI: 10.5539/ibr.v7n1p34
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Variation in Stock Returns due to Leverage in Exchange Istanbul

Abstract: The objective of this study is to test the existence of leverage premium in Exchange Istanbul during the period 2006 to 2013 by a four-factor asset pricing model. A sample of 470 firms is examined for this purpose. The results provide proof for negative effect of leverage on excess stock returns. However size mimicking portfolios have significant effect on the stock returns there is no evidence of value-effect in Exchange Istanbul. The significant negative relation between excess returns and leverage levels fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Gulnur Muradoglu and Sivaprasad's (2013) findings indicated that the variations in stock returns are better explained with the help of leverage mimicking portfolios as compared to the other asset pricing models. Koseoglu (2013) revealed that the leverage mimicking factor increased the descriptive ability of the model by providing a good description for crosssectional variations of stock returns in Istanbul Stock Exchange as compared to the Fama-French three-factor model. Boubaker et al (2018) found that leverage risk premium was positive for firms with high leverage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Gulnur Muradoglu and Sivaprasad's (2013) findings indicated that the variations in stock returns are better explained with the help of leverage mimicking portfolios as compared to the other asset pricing models. Koseoglu (2013) revealed that the leverage mimicking factor increased the descriptive ability of the model by providing a good description for crosssectional variations of stock returns in Istanbul Stock Exchange as compared to the Fama-French three-factor model. Boubaker et al (2018) found that leverage risk premium was positive for firms with high leverage.…”
Section: Review Of Literaturementioning
confidence: 99%